Critical thinking in evaluation instruments at BSE Indonesian language - Imam Safi'i; Wini Tarmini; Lili Wahdini (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
This article aims to describe the diversity of critical thinking contained in the evaluation instrument at Electronic School Book (BSE) Indonesian High School 2019/2020 Academic Year. This study uses a qualitative approach by applying the principles of content analysis. The data sources in this study were 541 evaluation instruments spread over eight teaching materials, namely compiling procedural texts, studying explanatory texts, managing information in lectures, studying life in short stories, preparing proposals, designing scientific papers, assessing works through reviews, and plays. The results showed that there were 189 evaluation instruments relevant to critical thinking aspects. Determines the credibility of a source and distinguishes between relevant and irrelevant as much as 22 or 11.6%. Identifies and evaluates unspoken assumptions and identifies biases that exist as many as 19 questions or 10.1%. Identifies the point of view as much as 100 questions or 52.9%, and evaluates the evidence offered to support as much as 7 questions or 3.7%. Based on the percentage of each critical thinking indicator, it can be concluded that efforts to develop critical thinking aspects in the evaluation instrument of the Indonesian Senior High School BSE have been developed well and are quite diverse.